Reporting quality of randomized controlled trials in otolaryngology: review of adherence to the CONSORT statement - Yu Qing Huang; Katsiaryna Traore; Badr Ibrahim; Maida J. Sewitch; Lily H. P. Nguyen (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Randomized controlled trials are the gold standard in medical and surgical research to assess the efficacy of therapeutic interventions. The reporting of these trials should be of high quality to allow readers’ appropriate interpretation and application. Methods The objectives of our study were to assess the extent to which the recent Otolaryngology – Head and Neck Surgery (ORL-HNS) randomized control trials in the top nine journals and in the top Canadian journal comply with the Consolidated Standards of Reporting Trials (CONSORT) statement, and to identify the CONSORT items most in need of improvement. Based on the impact factor and circulation number of 2014, the top nine Otolaryngology journals and the top Canadian Otolaryngology journal were selected and were searched to identify RCTs published in English and between 2010 and 2014. Two authors independently reviewed and extracted data using a standardized data extraction form constructed with the help of a medical librarian. Our outcome was to assess the adherence of articles reporting to the CONSORT items. Descriptive statistics were used. Results One hundred and eighty-two Otolaryngologic RCTs were identified in the top nine international journals and in the top Canadian journal. The inter-rater reliability between two raters was 0.32. The extent of adherence to CONSORT Statement ranged from 25 to 93.5% with a mean of 59.0% and a median of 59.4%. Only 6.5% of RCTs described the individual responsible for enrolling and assigning subjects and method of randomization; 32.4% reported the estimated effect size and precision; 40.6% reported a sample size calculation and 32.4% mentioned external validity or implications of the findings. Conclusion Findings revealed that the reporting of RCTs in the top nine ORL-HNS journals and in the top Canadian ORL-HNS journal is suboptimal. The quality of reporting can be improved by addressing the three CONSORT items found most deficient in this study namely, sample size calculations, estimated effect size and precision, and external validity.